2017
DOI: 10.1021/acs.jpclett.7b00045
|View full text |Cite
|
Sign up to set email alerts
|

Surface Polarization Model for the Dynamic Hysteresis of Perovskite Solar Cells

Abstract: The dynamic hysteresis of perovskite solar cells consists of the occurrence of significant deviations of the current density-voltage curve shapes depending on the specific conditions of measurement such as starting voltage, waiting time, scan rate, and other factors. Dynamic hysteresis is a serious impediment to stabilized and reliable measurement and operation of the perovskite solar cells. In this Letter, we formulate a model for the dynamic hysteresis based on the idea that the cell accumulates a huge quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
180
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(198 citation statements)
references
References 47 publications
18
180
0
Order By: Relevance
“…Both versions of DEM consistently reproduced experimental NH, including the dependence on the bias scan rate and the current overshoot in the reverse scan observed in several experimental studies [5,18,32], reproduced only in part by drift-diffusion based models [28]. The overshoot is consistent with a relaxation time of the polarization or charge accumulated at interfaces [30,31] at the beginning of the reverse scan measurement, indicating a relation between the pre-poling bias and the initial polarization. Furthermore, the dependence of the hysteresis on the bias scan rate is consistently described by the DEM: the hysteresis is diminished at very low and very high bias scan rates, being significant at intermediate ones; importantly, the short circuit current is enhanced with the increase of the bias scan rate.…”
Section: The Dynamic Electrical Model (Dem)supporting
confidence: 67%
See 2 more Smart Citations
“…Both versions of DEM consistently reproduced experimental NH, including the dependence on the bias scan rate and the current overshoot in the reverse scan observed in several experimental studies [5,18,32], reproduced only in part by drift-diffusion based models [28]. The overshoot is consistent with a relaxation time of the polarization or charge accumulated at interfaces [30,31] at the beginning of the reverse scan measurement, indicating a relation between the pre-poling bias and the initial polarization. Furthermore, the dependence of the hysteresis on the bias scan rate is consistently described by the DEM: the hysteresis is diminished at very low and very high bias scan rates, being significant at intermediate ones; importantly, the short circuit current is enhanced with the increase of the bias scan rate.…”
Section: The Dynamic Electrical Model (Dem)supporting
confidence: 67%
“…On the other hand, the crossing was observed experimentally [26] on aged samples with Ag counter electrodes, using a forward-reverse scan protocol starting from -0.1 V, which may be the effect of a small negative bias pre-poling, although not intentionally performed. The crossing of separately measured forward and reverse characteristics was also observed [31].…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Recent studies have shown that the accumulation of the ions and vacancies at interfaces changes the interfacial charge concentration and recombination rates, as well as the net photovoltage by setting up an electrostatic potential in addition to the built-in potential [23][24][25]. Since the electrostatic and built-in potentials have the same polarity (backward scan), the net open circuit voltage (VOC) of PSC devices is the sum of these potentials [24,26]. A generalized single diode model of a PSC, including the built-in and electrostatic potential formed due to the accumulation of ions and charges, is placed in a model previously discussed by Gottesman and others (Figure 1b) [24,26,27].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…(2), which describes the time evolution of P nl using a single relaxation time τ. A condition of the same type was used for the surface polarization voltage in the model proposed by Ravishankar et al [6], where it was conjectured that the cation migration together with an accumulation of holes is responsible for the hysteretic effects. According to Eq.…”
Section: Introductionmentioning
confidence: 99%